Functions of Some Capsular Polysaccharide Biosynthetic Genes in Klebsiella pneumoniae NTUH K-2044 - Ho, Jin-Yuan (Public Library of Science, 2011)
The growing number of Klebsiella pneumoniae infections, commonly acquired in hospitals, has drawn great concern. It has been shown that the K1 and K2 capsular serotypes are the most detrimental strains, particularly to those with diabetes. The K1 cps (capsular polysaccharide) locus in the NTUH-2044 strain of the pyogenic liver abscess (PLA) K. pneumoniae has been identified recently, but little is known about the functions of the genes therein. Here we report characterization of a group of cps genes and their roles in the pathogenesis of K1 K. pneumoniae. By sequential gene deletion, the cps gene cluster was first re-delimited between genes galF and ugd, which serve as up- and down-stream ends, respectively. Eight gene products were characterized in vitro and in vivo to be involved in the syntheses of UDP-glucose, UDP-glucuronic acid and GDP-fucose building units. Twelve genes were identified as virulence factors based on the observation that their deletion mutants became avirulent or lost K1 antigenicity. Furthermore, deletion of kp3706, kp3709 or kp3712 (ΔwcaI, ΔwcaG or Δatf, respectively), which are all involved in fucose biosynthesis, led to a broad range of transcriptional suppression for 52 upstream genes. The genes suppressed include those coding for unknown regulatory membrane proteins and six multidrug efflux system proteins, as well as proteins required for the K1 CPS biosynthesis. In support of the suppression of multidrug efflux genes, we showed that these three mutants became more sensitive to antibiotics. Taken together, the results suggest that kp3706, kp3709 or kp3712 genes are strongly related to the pathogenesis of K. pneumoniae K1.